Occurrente of Ophioglossum nudicaule L.f. and O.nudicaule Var. Macrorrhizum (Kze.) Clausen in Dharampur Forest - Inamdar, J. A.; Shah, J. J. (Indian Forester, 1967)
The occurrence of Ophioglossum nudicaule L.f. and O.nudieaule var. macrorrhizum (Kze.) Clausen is reported for the first time in Uharampur forests of Gujarat State. Incidentally the occurrence of O.nudieaule var. macrorrhizum (Kze.) Clausen is a new record.